Nigerians’ Attitudes Towards The Imitation Of Received Pronunciation Accent In Nigerians’ News Reading - Hussaini, Wakkai Hosanna (2023)
Using explanatory sequential design of mixed-methods, this research investigated Nigerians’ attitudes towards the imitation of Received Pronunciation accent in Nigerians’ news reading. There have been scarce field-based studies conducted on Nigerians’ attitudes towards English in Nigeria. The few studies conducted on the field only looked at Nigerians’ attitudes towards Received Pronunciation without focusing on the Nigerians’ attitudes towards the imitation of Received Pronunciation accent in Nigerians’ news reading. Therefore, the Nigerians’ attitudes towards the imitation of Received Pronunciation accent in Nigerians’ news reading formed the object of this study, with the objective of evaluating both the inter-speaker and intra-speaker attitudes of Nigerians towards it. The questionnaire participants were 236, selected from the class of Nigerian public university lecturers. While the interview participants were 24, 14 drawn from the questionnaire participants and 10 from the Nigerian newsreaders on television. The study was conducted within the theoretical and conceptual frameworks of sociolinguistics and language attitude respectively. From the quantitative data, results showed that participants liked and preferred listening to the imitation of Received Pronunciation by Nigerians in news reading over other English accents used in news reading. Yet, for the sake of their identities, the participants disagreed that they imitate the Nigerian newsreaders’ accent.